Thermal and fire retardancy studies of clay‐modified unsaturated polyester/glass fiber composites. Issue 12 (19th November 2015) - Romanzini, Daiane; Cuttica, Fabio; Frache, Alberto; Zattera, Ademir J.; Amico, Sandro C.
Abstract : The aim of this study was to investigate the effect of new, cation‐exchanged, and silane modified montmorillonite nanoclays fillers on thermal, mechanical and flammability characteristics of polyester/glass fiber composites in comparison with composites prepared with calcium carbonate filler. The coefficient of thermal expansion showed reduced values for silane‐modified samples. All the composites decomposed at lower temperatures in air and their degradation behavior differed from those exposed to nitrogen. The glass fibers acted as a physical barrier before combustion and the catalytic effect of the clay was less pronounced for silane‐modified samples. The peak of heat release and linear burning rate for the silane‐modified Cloisite 30B sample was reduced. However, the limiting oxygen index did not show significant changes. In general, consequent to clay addition, these composites showed improved fire performance, shorter fire duration and slower fire growth and maintained better mechanical properties than those with calcium carbonate filler. POLYM. COMPOS., 38:2743–2752, 2017. © 2015 Society of Plastics Engineers